Tumor Volume Analysis as a Predictive Marker for Prolonged Survival in Anaplastic Lymphoma Kinase–rearranged Advanced Non–Small Cell Lung Cancer Patients Treated With Crizotinib. Issue 2 (March 2020) - Hida, Tomoyuki; Dahlberg, Suzanne E.; Lydon, Christine A.; Hatabu, Hiroto; Johnson, Bruce E.; Awad, Mark M.; Nishino, Mizuki
Abstract : Purpose: Targeted inhibition of anaplastic lymphoma kinase (ALK) has been widely used for the treatment of advanced non–small cell lung cancer (NSCLC) with ALK rearrangements. We performed tumor volume analysis of ALK-rearranged advanced NSCLC treated with crizotinib to identify an early predictive marker for prolonged survival. Materials and Methods: Cases of 42 patients with ALK-rearranged advanced NSCLC (16 men, 26 women; median age: 55.7 y) treated with crizotinib as their first ALK-directed therapy were retrospectively studied. Tumor volume measurements of dominant lung lesions were performed on baseline computed tomography and follow-up computed tomography at 8 weeks of therapy. The relationships between the 8-week volume change (%) and overall survival (OS) were investigated. Results: The 8-week tumor volume change ranged from −99.3% to 117.5% (median: −57.7%). Using the 25th percentile of the 8-week volume change of −74%, 11 patients with >74% volume decrease at 8 weeks had a significantly longer OS compared with 31 patients with ⩽74% decrease (median OS: 92.0 vs. 22.8 mo; P =0.0048). In multivariable analyses using Cox proportional hazards models, the 8-week volume decrease of >74% was significantly associated with longer OS (hazard ratio=0.14, 95% confidence interval: 0.03-0.59; Cox P =0.008) after adjusting for tumor stage (stage IV vs. recurrent NSCLC, hazard ratio=5.6, 95% confidence interval: 1.29-24.3; P =0.02). Conclusions: The 8-week tumor volume decrease of >74% is significantly associated with longer OS in patients with ALK-rearranged NSCLC treated with crizotinib.